Workplace bullying in Malaysia: incidence, consequences and role of organisational support - Hassan, Arif; Sadiq Al Bir, Ahmad Talib; Hashim, Junaidah (2015)
Workplace bullying is an anti-social behaviour which is defined as continuous harassment or “mobbing” of individual employee experienced for a relatively longer period of time. This may take several forms such as constant abuse, offensive remarks or teasing, ridicule, social exclusion, harassment, physical violence etc. The situation may be damaging to the wellbeing and job performance of the employee. However, if the organisation provided necessary support to the employee the effect of bullying could be mitigated. The paper examines these issues in selected Malaysian organisations. A sample of 231 employees representing different industry, size, gender, age, experience and job position responded to a self-rated questionnaire which measured the study variables, namely workplace bullying, psychological strain, self-rated job performance, and organisational support. Result indicated that nearly 14 % employees faced bullying incidents either weekly or daily. Such incidents resulted in higher psychological strain and lower job performance. Role of psychological support was positive in promoting performance and reducing strain.